2018
DOI: 10.1007/s11440-018-0641-x
|View full text |Cite
|
Sign up to set email alerts
|

Shear strength behavior and parameters of microbial gellan gum-treated soils: from sand to clay

Abstract: Microbial biopolymers have recently been introduced as a new material for soil treatment and improvement. Biopolymers provide significant strengthening to soil, even in small quantities (i.e., at 1/10th or less of the required amount of conventional binders, such as cement). In particular, thermo-gelating biopolymers, including agar gum, gellan gum, and xanthan gum, are known to strengthen soils noticeably, even under water-saturated conditions. However, an explicitly detailed examination of the microscopic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
74
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(78 citation statements)
references
References 79 publications
4
74
0
Order By: Relevance
“…3d. All kaolinite-sand soils show a peak LL DI at m b /m c = 0.5%, which is in accordance with the previous finding from Chang and Cho (2019) addressing m b /m c to mainly govern biopolymer-clay matrix formation and relevant shear strength properties (i.e., cohesion and friction angle) (Chang and Cho 2019). As the content of xanthan gum increases, xanthan gum initiates kaolinite aggregation via ionic or hydrogen bonding (Laird 1997;Sastry et al 1995;Theng 2012), which accompanies a decrease in LL DI (③ in Fig.…”
Section: Ll DI Ll B and Ll K Of Xanthan Gum-treated Kaolinite-sansupporting
confidence: 91%
See 2 more Smart Citations
“…3d. All kaolinite-sand soils show a peak LL DI at m b /m c = 0.5%, which is in accordance with the previous finding from Chang and Cho (2019) addressing m b /m c to mainly govern biopolymer-clay matrix formation and relevant shear strength properties (i.e., cohesion and friction angle) (Chang and Cho 2019). As the content of xanthan gum increases, xanthan gum initiates kaolinite aggregation via ionic or hydrogen bonding (Laird 1997;Sastry et al 1995;Theng 2012), which accompanies a decrease in LL DI (③ in Fig.…”
Section: Ll DI Ll B and Ll K Of Xanthan Gum-treated Kaolinite-sansupporting
confidence: 91%
“…However, application of biopolymers to soil treatment requires considerations of the biopolymer rheology, phase transfer with water content variation, biopolymer to soil ratio, soil type, and pore-fluid condition, which affects the biopolymer-soil matrix formation (Chang and Cho 2019;Chang et al 2015cChang et al , 2017. Biopolymer-treated soils with a high water content show low strength due to the low viscous biopolymer hydrocolloids surrounding soil particles (Chang et al 2017), while dehydration increases the soil strength due to the condensation of the biopolymer hydrogels forming high-tensile-strength biofilms through the soil particulate network (Chang et al 2016a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gellan gum in the polysaccharide group is a high-molecular-weight polymer produced by the bacterium Sphingomonas elodea (formerly known as Pseudomonas elodea) [27,31,32]. Also, gellan gum is generated by four molecules: (1,3)-β-D-glucose, (1,4)-β-D-glucuronic acid, (1,4)-β-D-glucose, and (1,4)-α-L-rhamnose as shown in Figure 3 [27].…”
Section: Gellan Gummentioning
confidence: 99%
“…The strength of sand-clay mixtures has been reported to increase by the addition of biopolymers unlike that of pure sand or clay alone Cho, 2018, Cabalar et al, 2018). The synergistic effect is due to the flocculation of fine particles as well as the interconnection between fine and coarse particles (Chang and Cho, 2018). Studies have also demonstrated the importance of complete drying in order to achieve maximum strength for biopolymer treated soils (Swain et al, 2018) as the strength of biopolymers has been found to be dependent on water content (Chang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%